1982
DOI: 10.3109/03093648209166772
|View full text |Cite
|
Sign up to set email alerts
|

The physical effect of lumbar spinal supports

Abstract: A study has been performed to investigate the physical effects of lumbar spinal supports. Two groups were studied, a group of normal male subjects and a group of male low back pain patients. Five different spinal supports were investigated and their effects upon the skin temperature, spinal movements and intra-abdominal pressures of these individuals were examined. The results show surprisingly similar patterns for the widely varying designs of support. The findings also suggest that the longer term wearing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Elastic supports were studied in four studies. 5,13,15,31 Combined effect sizes of these studies were 1.01 (95% CI: 0.10 -1.92) for flexion-extension, 0.84 (95% CI: 0.24 -1.43) for lateral bending, and 1.81 (95% CI: Ϫ0.22-3.84) for rotation.…”
Section: Changes In Body Posture or Movements Inmentioning
confidence: 95%
See 2 more Smart Citations
“…Elastic supports were studied in four studies. 5,13,15,31 Combined effect sizes of these studies were 1.01 (95% CI: 0.10 -1.92) for flexion-extension, 0.84 (95% CI: 0.24 -1.43) for lateral bending, and 1.81 (95% CI: Ϫ0.22-3.84) for rotation.…”
Section: Changes In Body Posture or Movements Inmentioning
confidence: 95%
“…17,26,27,37 Reported results in all four showed an increase in IAP, but electromyogram in the erector spinae muscles consistently decreased in only one. 27 In seven studies, investigators measured IAP but did not simultaneously record an electromyogram of the back muscles (Table 3), 15,16,24,43,42,52,62 Investigators in two of these studies reported an increase in IAP in subjects using lumbar supports, 16,52 in two studies they reported inconsistent results, 15,43 and three they found no effect of a lumbar support on IAP. 24,42,62 Separate meta-analyses for studies on electromyogram of erector spinae muscles and on IAP were conducted.…”
Section: Reduction In Back Muscle Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have examined the effects of spinal orthoses on intervertebral motion [5][6][7], gross spinal motion [8], and restriction of the spine in positions of maximal trunk flexion-extension-rotation [6][7][8][9][10]. Association of results from these evaluations to the spinal motions that occur during walking is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In the thoracolumbar spine, orthoses reduce gross spinal motion to varying degrees depending on their de sign. 4,6,13,16,25,29,32 Overall, the body cast is most effective in limiting motion in all planes of the thoracolumbar and lumbar spine. 13,32 The Jewett hyperextension brace is ef fective in limiting instability in flexion but not in rotation or lateral bending.…”
mentioning
confidence: 99%